PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP EFEKTIVITAS KERJA PADA PT. ASRI GRIYA UTAMA, PROJECT HOLLAND VILLAGE MANADO - Christien Adriani Karambut (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2018)
Safety and health of work are variable that can provides comfortableatmosphere to doing our work. Moreover, the work he does is risky. It takesprovisions that regulate safety and health so that employees can perform theirduties calmly. For that, every organization needs to pay attention to both aspects.The occurrence of work accidents certainly cause a very big problem for thecompany as well as for the workers themselves because if the safety and healthwork is not going well then the effectiveness of employees will decrease and resultin delayed work.This study aims to know whether safety and health of work effect on theeffectiveness of work at PT. Asri Griya Utama. The data used in this study wereobtained from the questionnaires distributed in each employee of PT. Asri GriyaUtama. This research method using quantitative method, with total population 46employees and sample which writer use is saturated sampling, where all memberof population used as sample.The results of this study obtain results where employee safety variables andoccupational health work well enough so that the impact on the effectiveness ofwork that is run less in accordance with the provisions. Through it can be seenthat the safety and health of employees greatly affect the effectiveness of thecompany's work. Therefore, the need for attention from the leadership of thecompany in order to be more priority of safety and health of each employee.